Psychosocial work environment beyond WEIRD: meta-analytic and psychometric evidence on the Job Content Questionnaire - García-Selva, Adrián; Martín-del-Río, Beatriz; Leiva-Bianchi, Marcelo (Frontiers in Psychology, 2025)
BackgroundThe psychosocial work environment significantly impacts employee well-being and performance. Among the most recognized models for assessing psychosocial risk factors is the Job Demand-Control-Support (JDCS) model, which posits that psychological demands, job control, and social support are core determinants of work-related stress. Although extensively studied, research on its measurement tools—particularly the Job Content Questionnaire (JCQ)—has been disproportionately conducted in WEIRD countries, raising questions about cross-cultural validity.ObjectiveThis study aimed to (I) evaluate the reliability of JCQ dimensions across cultures through a meta-analytic approach and (II) validate a 15-item short version of the JCQ in a large and culturally distinctive Spanish sample.MethodsA meta-analysis of 21 studies (N = 21,732) from WEIRD and non-WEIRD countries assessed the internal consistency of psychological demands and job control dimensions. Additionally, an empirical validation was conducted with 860 Spanish workers using exploratory structural equation modeling (ESEM) to test factorial structure, reliability, and measurement invariance across gender, job level, and educational background.ResultsMeta-analytic results showed moderate to high internal consistency for job control (α = 0.737) and psychological demands (α = 0.603), with higher reliability in WEIRD populations for job control. The Spanish validation supported a four-factor ESEM model with excellent fit and invariance across demographic groups. All dimensions showed strong composite reliability and convergent validity.ConclusionThis research confirms the robustness of the JCQ’s core constructs and supports the use of a concise, psychometrically sound version of the instrument across diverse sociocultural contexts. It also advances equitable psychometric practices by bridging WEIRD and non-WEIRD research efforts.